Applied linguistics for teachers of culturally and linguistically diverse learners - Erdogan, Nabat, 1979-; Wei, Michael, 1968- (Information Science Reference, 2019)
"This book examines linguistics and its application in English language teaching and learning. It bridges the gap between linguistic theory and its application in practice in order to prepare effective English for Speakers of Other Languages (ESOL) teachers and professionals"--